Evaluation of quick and precise diagnostic tests for bluetongue - Mishra, S; Mehrotra, M L (The Indian Journal of Animal Sciences, 2012)
The quick and precise diagnostic tests for bluetongue were evaluated. Among the serological tests used to detect antibody,agar-gel precipitation test was more convenient and economical, whereas enzyme linked immunosorbent assay was more sensitive.Serum neutralization test was used to detect type-specific antibody. Viral antigen was detected by fluorescent antibodytechnique and immunoperoxidase test.